TO THE MEMORY OF KAZALY KAMALOVICHA KAZALIEV, A MASTER AND A MENTOR - N.M. Velizhanov (Овощи России)
On 9 August, 2011 K.K. KAZALIEV, renowned worker of agriculture of Russian Federation, honored economist of Republic of Dagestan, researcher (PhD), director of Dagestan Experimental Station of Vegetable Breeding and Viticulture passed away at the age of 62.